Evaluation of The Implementation of Inclusive Education in the Inclusive School of Pajang 1 Surakarta - Nugraha, Andre Eksaputra; Minsih, M; Wulandari, Murfiah Dewi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to evaluate the implementation of inclusive education at SD Negeri Pajang 1 Surakarta, focusing on both its supporting factors and the challenges encountered. Methodology: The research employed a qualitative approach, utilizing in-depth interviews and direct observations to gather primary data. Secondary data were obtained through documentation studies. The participants included school principals, teachers, and other relevant stakeholders involved in inclusive education. Results: The findings indicate that the implementation of inclusive education at SD Negeri Pajang 1 Surakarta is supported by adequate facilities and a strong commitment from the principal and teachers. However, several challenges persist, including limited teacher competence in handling children with special needs and the necessity for additional support for these students. Applications/Originality/Value: This study highlights the importance of ongoing teacher training, enhanced collaboration between teachers and parents, and regular monitoring and assessment of children with disabilities. These recommendations are essential for improving the quality and sustainability of inclusive education in elementary schools. The study contributes to the growing body of literature on inclusive practices in Indonesian educational settings.